Factor Structure of Psychological Security Scale "A field study on a sample of Tishreen University students" - شريبه بشرى (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The present research was designed to investigate the factor structure of Shkeer’s psychological security scale (2005), by using the exploratory factor analysis. the psychological security scale of shkeer consists of four dimensions: (individual building and future vision (14 items), general and practice life (18 items), temperament (10 items), social relationships and social interaction (12 items). The researcher used the descriptive method, and the research sample was chosen randomly, while the data were collected from (415) students of Tishreen University. The research revealed that the psychological security consists of six factors, which had explained (52.91%) of total variance of items: The first factor: future vision and includes 14 items. The second factor: social relationships and includes 7 items. The third factor: temperament and includes 7 items. The fourth factor: practice life and includes 5 items. The fifth factor: general life and includes 5 items. The sixth factor: social interaction and includes 4 items. The researcher suggests that more studies should be done to investigate the factor structure of the psychological security scale on different Syrian samples.and proposes to study the relationship between psychological security and some variables.